Cereblon Regulates the Proteotoxicity of Tau by Tuning the Chaperone Activity of DNAJA1 - Akber, Uroos; Jo, Heeji; Jeon, Seungje; Yang, Seung-Joo; Bong, Sunhwa; Lim, Sungsu; Kim, Yun Kyung; Park, Zee-Yong; Park, Chul-Seung (Society for Neuroscience, 2021)
Protein aggregation can induce explicit neurotoxic events that trigger a number of presently untreatable neurodegenerative disorders. Chaperones, on the other hand, play a neuroprotective role because of their ability to unfold and refold abnormal proteins. The progressive nature of neurotoxic events makes it important to discover endogenous factors that affect pathologic and molecular phenotypes of neurodegeneration in animal models. Here, we identified microtubule-associated protein tau, and chaperones Hsp70 (heat shock protein 70) and DNAJA1 (DJ2) as endogenous substrates of cereblon (CRBN), a substrate-recruiting subunit of cullin4-RING-E3-ligase. This recruitment results in ubiquitin-mediated degradation of tau, Hsp70, and DJ2. Knocking out CRBN enhances the chaperone activity of DJ2, resulting in decreased phosphorylation and aggregation of tau, improved association of tau with microtubules, and reduced accumulation of pathologic tau across brain. Functionally abundant DJ2 could prevent tau aggregation induced by various factors like okadaic acid and heparin. Depletion of CRBN also decreases the activity of tau-kinases including GSK3α/β, ERK, and p38. Intriguingly, we found a high expression of CRBN and low levels of DJ2 in neuronal tissues of 5XFAD and APP knock-in male mouse models of Alzheimer’s disease. This implies that CRBN-mediated DJ2/Hsp70 pathway may be compromised in neurodegeneration. Being one of the primary pathogenic events, elevated CRBN can be a contributing factor for tauopathies. Our data provide a functional link between CRBN and DJ2/Hsp70 chaperone machinery in abolishing the cytotoxicity of aggregation-prone tau and suggest that Crbn−/− mice serve as an animal model of resistance against tauopathies for further exploration of the molecular mechanisms of neurodegeneration.